A pilot study to assess the effect of a fibre and mineral formulation on satiety and satiation when taken as part of a calorie restriction diet in overweight and obese women. (November 2020) - Keleszade, Enver; Willner, Tamara; Patterson, Michael; Trangmar, Steven; Kolida, Sofia; Costabile, Adele
Graphical abstract: Highlights: Fibre and mineral formulation positively affect anthropometric parameters and blood pressure. Fibre and mineral formulation'intake improve mood, cravings and hunger scores. Regular intake of SlimBiome® positive impact on the gut microbiome. Abstract: An approach that combines weight loss with additional health benefits is very desirable. Glucomannan is a dietary fibre that expands in the stomach, creating the feeling of fullness, while chromium can regulate insulin response. Oligofructose is a non-digestible prebiotic fibre with well-established bifidogenic properties that may also have a role in regulating satiety and systemic inflammation. The aim of this 4-week pilot human intervention was to investigate the effect of agglomerated glucomannan, oligofructose and chromium, as part of a calorie restricted diet plan, on weight loss, satiety, satiation, mood and gut microbiota in 12 females (18–65 years, BMI 25–35 kg/m 2 ). Significant reductions were observed in the anthropometric parameters and systolic blood pressure at the end of trial along with a positive impact on gut microbiota and food cravings. This pilot study suggests that this dietary combination, within an energy restricted, diet may be beneficial in managing obesity related health outcomes.